2022
DOI: 10.3390/ijerph191912236
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Cyber-Ostracism and Adolescents’ Non-Suicidal Self-Injury: Mediating Roles of Depression and Experiential Avoidance

Abstract: Based on the experiential avoidance model, the current study aims to test the relationship between cyber-ostracism and adolescents’ non-suicidal self-injury and to explore the mediating roles of depression and experiential avoidance. A sample of 1062 middle school students completed questionnaires on cyber-ostracism, depression, experiential avoidance, and self-injurious behavior. The results showed that cyber-ostracism, depression, experiential avoidance, and non-suicidal self-injury were positively correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…With the popularization of the Internet, online socialization among college students has become a widespread phenomenon. Due to the convenience and breadth of online social interaction, as well as its characteristics such as anonymity, lack of social cues, and fast spread of media, online ostracism may cause more severe harm to individuals compared to face-to-face ostracism ( 52 ). Ostracism experiences are often closely related to individuals’ aggression tendencies ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the popularization of the Internet, online socialization among college students has become a widespread phenomenon. Due to the convenience and breadth of online social interaction, as well as its characteristics such as anonymity, lack of social cues, and fast spread of media, online ostracism may cause more severe harm to individuals compared to face-to-face ostracism ( 52 ). Ostracism experiences are often closely related to individuals’ aggression tendencies ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the short term, depression can negatively impact adolescents’ academic performance, social functioning, and interpersonal relationships ( Chavez et al, 2023 ). In the long term, adolescents are prone to self-injury, suicide, and other behavioral problems once they are depressed ( Ding et al, 2022 ; Neslusan et al, 2023 ), and at the risk of developing related psychiatric disorders in adulthood ( Robin et al, 2017 ). Therefore, it is particularly important to improve the mental health level of adolescents, to prevent and reduce adolescent depression.…”
Section: Introductionmentioning
confidence: 99%
“…In a report by the World Health Organization, it was stated that suicide is the second leading cause of death among young people aged 15–29 worldwide ( 1 ), where non-suicidal self-injury (NSSI) is an important predictor of suicidal behavior ( 2 ), and NSSI has become an increasingly serious global public health problem ( 3 ). Non-suicidal self-injury is defined as: an act in which an individual intentionally injures and directly damages his or her own body tissues without suicidal intent, commonly by cutting, stabbing, or excessive friction, which can cause bleeding and bruising, and this behavior is socially unacceptable ( 4 , 5 ). In recent years, the prevalence of NSSI in the adolescent population and its harmful effects have received widespread attention, and a Meta-analysis showed that the percentage of Chinese secondary school students who had experienced NSSI behaviors was 22.37% ( 6 ).…”
Section: Introductionmentioning
confidence: 99%